Constructing A Test for Assessing Higher Order Thinking Skills of High School Students on Reproductive System - Walid, Ahmad; Sajidan, Sajidan; Ramli, Murni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The research aims to constructthe paper test to assess the higher order thinking skills of high school students. The research was designed based on Borg and Gall research method. Firstly, test from national examination, formative and summative test, and also the test written inÂ  high school Biology textbook commonly used in Surakarta were analyzed, and it found that most of the test are to measure the lower order thinking skills. Draft of HOTS on reproductive system then been formulated, and validated by three experts and teachers on three aspects, i.e. language, content, and construction of the instrument. The test was divided into two packages, A and B, each consists of 15-multiple choice items, and 5 essays. Test have to be finished in 60 minutes. To test the visibility of the instrument, a First Trial had been done to a small number of students. Obtained data was quantitively analyzed using theMicroCatITEMAN program version 3.00 for the multiple choice to check reliability, level of difficulty, discriminating index and effectiveness of the distractor, while the essay was analyzed using the Microsoft Excel for reliability, level of difficulty, as well as discriminating index. The result shows that A type test consists of 43 % of items were accepted, 24% item revised, and 33 % rejected. While the B test package has 62% item were accepted, 33 % item were revised, and 5 % item were rejected.Keywords:Â Assessment , High Order Thinking Skills, Reproductive System